Efektivitas Pengendalian Gulma Epifit Beringin (Ficus Benjamina) Menggunakan Herbisida Campuran Glifosat dan Metil Metsulfuron dengan Cara Penginfusan Akar - Sihotang, Dodi Pransiska; Parinduri, Sulthon (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The epiphytic banyan weed (Ficus benjamina) is a major problem in oil palm plantations as it interferes with harvesting and reduces productivity. One effective control method is the root infusion technique using systemic herbicides. This study aimed to determine the most effective herbicide concentration and evaluate the effectiveness of the root infusion method. The research was conducted in a smallholder plantation in Rimbun Village, Sipispis District, Serdang Bedagai Regency from August to September 2025. A non-factorial Randomized Block Design (RBD) with four treatments and four replications was used, consisting of P0 (control), P1 (glyphosate 8 ml/L + metsulfuron methyl 4 g/L), P2 (glyphosate 10 ml/L + metsulfuron methyl 6 g/L), and P3 (glyphosate 12 ml/L + metsulfuron methyl 8 g/L). The observed parameter was weed mortality percentage up to 30 days after application. Data were analyzed using ANOVA followed by DMRT at 5%. The results showed that herbicide treatments significantly affected weed mortality. Treatment P3 achieved the fastest mortality (100%) at 17 days, followed by P2 at 27 days and P1 at 29 days, while the control showed no mortality. Increasing herbicide concentration amlelerated weed death. The root infusion method proved effective in enhancing herbicide absorption. Therefore, P2 is recommended as the optimal and efficient dose.